A novel SOX10 variant in a Japanese girl with Waardenburg syndrome type 4C and Kallmann syndrome - Hamada, Junpei (Hum Genome Var, 2020)
We report the first case of Waardenburg syndrome type 4C and Kallmann syndrome in the same person. The patient, a Japanese girl, presented with bilateral iris depigmentation, bilateral sensorineural hearing loss, Hirschsprung disease, hypogonadotropic hypogonadism, and anosmia. We identified a novel SOX10 variant, c.124delC, p.Leu42Cysfs*67.